2018
DOI: 10.3847/1538-4357/aabadb
|View full text |Cite
|
Sign up to set email alerts
|

HST Grism Confirmation of 16 Structures at 1.4 < z < 2.8 from the Clusters Around Radio-Loud AGN (CARLA) Survey

Abstract: We report spectroscopic results from our 40-orbit Hubble Space Telescope slitless grism spectroscopy program observing the 20 densest Clusters Around Radio-Loud AGN (CARLA) candidate galaxy clusters at 1.4<z<2.8. These candidate rich structures, among the richest and most distant known, were identified on the basis of [3.6]-[4.5] color from a 408hr multi-cycle Spitzer program targeting 420 distant radio-loud AGN. We report the spectroscopic confirmation of 16 distant structures at 1.4<z<2.8 associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(120 citation statements)
references
References 137 publications
11
109
0
Order By: Relevance
“…In this study, we identify an environmental dependence on the star-forming galaxy main sequence at 1.0 < z < 1.5, where cluster galaxies have lower log ∆SFR MS at fixed stellar mass than their counterparts in the field by a factor of 1.4, with a significance in log ∆SFR MS of ∼ 3.3σ across all stellar masses, but strongest at lower stellar masses ( Figure 5). Our findings are in good agreement with those of Noirot et al (2018), who find a significant suppression in the main sequence of the CARLA cluster sample, relative to the field sample of Whitaker et al (2014) at z ∼ 1.5. However, our results appear to differ somewhat from some other studies at a comparable redshift.…”
Section: Environmental Dependence Of the Star-forming Main Sequencesupporting
confidence: 91%
“…In this study, we identify an environmental dependence on the star-forming galaxy main sequence at 1.0 < z < 1.5, where cluster galaxies have lower log ∆SFR MS at fixed stellar mass than their counterparts in the field by a factor of 1.4, with a significance in log ∆SFR MS of ∼ 3.3σ across all stellar masses, but strongest at lower stellar masses ( Figure 5). Our findings are in good agreement with those of Noirot et al (2018), who find a significant suppression in the main sequence of the CARLA cluster sample, relative to the field sample of Whitaker et al (2014) at z ∼ 1.5. However, our results appear to differ somewhat from some other studies at a comparable redshift.…”
Section: Environmental Dependence Of the Star-forming Main Sequencesupporting
confidence: 91%
“…To the best of our knowledge this proto-cluster candidate has never been reported in previous work. If confirmed spectroscopically, it will be one of the most distant proto-clusters discovered around radio galaxies (see also e.g., Noirot et al 2016Noirot et al , 2018. Castignani et al (2014a) searched for overdensities associated with z > 1 COSMOS-FRI radio galaxies within the proto-cluster catalog of Diener et al (2013), which was constructed using spectroscopic redshift information from the zCOSMOS-deep survey (Lilly et al 2007, Lilly et al, in prep.).…”
Section: Low-richness Structuresmentioning
confidence: 99%
“…At z 1.5 several studies targeting galaxy overdensities have found evidence for cases where the SFRs of member galaxies are comparable or enhanced relative to field galaxies (e.g., Tran et al 2010;Strazzullo et al 2013;Santos et al 2015;Webb et al 2015;Wang et al 2016) indicating that environment did not always strictly act to quench star-formation. These observations mainly pertain to cluster cores, in other works cluster members have shown systematically lower SFRs than similar mass counterparts among field galaxies at these redshifts (Noirot et al 2018). Unfortunately, however, understanding the nature of a transition in the SFR-density relation and the exact epoch at which it occurs is still debated with some studies finding positive correlations, some finding negative correlations, and others no significant correlation at intervening redshifts (e.g., Elbaz et al 2007;Cooper et al 2008;Popesso et al 2011;Patel et al 2011;Grützbauch et al 2011;Muzzin et al 2012;Koyama et al 2013;Ziparo et al 2014;Lin et al 2014;Darvish et al 2016).…”
Section: Introductionmentioning
confidence: 99%